Development of E-Supplement Biomordant from Several Species of Ferns (Pteridophyta) as A Teaching Material for Green Chemistry Course - Hariyanti, Weni; Masriani, Masriani; Sasri, Risya; Sapar, Ajuk; Erlina, Erlina (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The purpose of this study was to determine the feasibility of Green Chemistry E-Supplement with material Biomordant from Several Species of Ferns (Pteridophyta). The method used in this research is Research and Development (R&D). The e-supplement teaching material development model used is ADDIE. The subject of this research is Green Chemistry E-Supplement with material Biomordant from Several Species of Ferns (Pteridophyta). The data collection techniques used were direct communication and measurement techniques. The research instrument used was a feasibility assessment sheet and data analysis using a Likert scale. The feasibility of Â e-supplement was assessed by two validators. The final results of the feasibility assessment in the aspects of material, media, and language obtained a percentage of 98%. So, it can be concluded that the Green Chemistry E-Supplement with material Biomordant from Several Species of Ferns (Pteridophyta) is very feasible.